(untitled) - Pham, Thanh Huyền (Cần Thơ, 2018)
This research is conducted to investigate the extent to which non-English major college students think they can achieve English proficiency level standard (level B1). Find out the factors preventing non-English major college students from achieving that required proficiency level standard.
Keywords: Tiếng Anh,English language; Học và dạy học,Study and teaching